THE ROLE OF ICT IN THE SPEED AND ACCURACY OF DECISIONS IN THE DIGITAL BUSINESS ENVIRONMENT - Alrobby Nurilham; Muhammad Irwan Padli Nasution (Yayasan Bayt Shufiya Nusantara, 2025)
In today’s rapidly evolving digital landscape, Information and Communication Technology (ICT) plays a fundamental role in shaping how individuals and organizations operate. The integration of advanced technologies such as artificial intelligence (AI), the Internet of Things (IoT), and blockchain has transformed traditional business processes into dynamic, data driven systems capable of responding quickly to market changes. As digitalization becomes embedded in nearly every aspect of modern life, businesses increasingly rely on ICT to streamline operations, improve efficiency, and strengthen their competitive position. This study aims to explore the concept of ICT and examine how its implementation influences the speed and accuracy of strategic decision making in the digital business environment. A qualitative descriptive method was employed to gain in depth insights into these phenomena. Data were collected from various credible sources, including academic books, journals, and relevant online publications, allowing for comprehensive analysis. The findings highlight that ICT not only accelerates decision making but also enhances decision quality through real time data availability, automated processing, and improved communication flow within organizations.